2021
DOI: 10.3389/fnagi.2021.650047
|View full text |Cite
|
Sign up to set email alerts
|

Roles and Mechanisms of Gut Microbiota in Patients With Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common age-related progressive neurodegenerative disease, characterized by a decline in cognitive function and neuronal loss, and is caused by several factors. Numerous clinical and experimental studies have suggested the involvement of gut microbiota dysbiosis in patients with AD. The altered gut microbiota can influence brain function and behavior through the microbiota–gut–brain axis via various pathways such as increased amyloid-β deposits and tau phosphorylation, neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 221 publications
1
56
0
Order By: Relevance
“…Recent advances in gut microbiota studies have expanded beyond simply profiling microbiota compositions and have been increasingly characterizing microbial functions by using functional meta-omics approaches and deciphering the cross-talk between the gut microbiota and host in detail Ling et al, 2022 . With these developed omics techniques, our previous studies have found that the gut microbiota dysbiosis leading to changes in the bidirectional relationship between gut microbiota and the nervous system is linked to the pathogenesis of several neuropsychiatric diseases, such as major depressive disorder, Alzheimer’s disease, Parkinson’s disease, multiple sclerosis and so on ( Jiang et al., 2015 ; Ling et al., 2020a ; Ling et al., 2020c ; Ling et al., 2020d ; Sun et al., 2020 ; Sun et al., 2021 ; Wu et al., 2021 ). Different from previous genetic and environmental findings, the alterations of the gut microbiota provide novel insights into the pathogenesis of these neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in gut microbiota studies have expanded beyond simply profiling microbiota compositions and have been increasingly characterizing microbial functions by using functional meta-omics approaches and deciphering the cross-talk between the gut microbiota and host in detail Ling et al, 2022 . With these developed omics techniques, our previous studies have found that the gut microbiota dysbiosis leading to changes in the bidirectional relationship between gut microbiota and the nervous system is linked to the pathogenesis of several neuropsychiatric diseases, such as major depressive disorder, Alzheimer’s disease, Parkinson’s disease, multiple sclerosis and so on ( Jiang et al., 2015 ; Ling et al., 2020a ; Ling et al., 2020c ; Ling et al., 2020d ; Sun et al., 2020 ; Sun et al., 2021 ; Wu et al., 2021 ). Different from previous genetic and environmental findings, the alterations of the gut microbiota provide novel insights into the pathogenesis of these neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This improvement could also be related to the interactions between gut microbiota and mitochondrial oxidative stress, which participates in cardiac fibrosis in the context of obesity [ 23 ]. In fact, the role of microbiota dysbiosis has been reported not only in obesity but also in other pathological scenarios, including neurodegenerative diseases [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased abundance of Gram-negative intestinal bacteria such as Bacteroides in AD patients may result in increased LPS translocation from the gut to the systemic circulation, which may contribute to AD pathology through the stimulation of systemic inflammation. Additional studies have confirmed AD-related decreases in microbiota richness and diversity and clearly evidence of different compositions in patients when compared to cognitively normal controls or MCI (reviewed in [ 91 ]). Yet, since the two pioneering clinical studies of microbiota in AD, performed in USA [ 88 ] and Italy [ 92 ] in 2017, an additional study from USA [ 93 ] and six studies from China [ 94 99 ] have been published.…”
Section: Cognitive Dysfunction and Microbiota In Alzheimer’s Diseasementioning
confidence: 93%